Efficacy of synbiotic and probiotic treatments on acute watery diarrhea in children - Ani Isti Rokhmawati; Wahyu Damayanti; Madarina Julia (Indonesian Pediatric Society, 2012)
Background In developing countries, acute watery diarrhea isa common cause of morbidity and mortality in children. Givingsynbiotics or probiotics may decrease the severity of diarrhea.Objective To compare the efficacy of synbiotics and probioticsin decreasing the frequency of diarrhea, shortening the duration,and increasing patient body weight.Methods This was a doubleô€€·blind, randomized clinical trial tocompare the effects of synbiotic vs probiotic treatment in childrenaged 6ô€€·59 months v.ith acute watery diarrhea. This study wasperformed from October to December 2010 in two hospitals inCentral Java. Subjects received either synbiotics or probioticstv.ice daily for five days. The measured outcomes were durationof diarrhea, daily frequency of diarrhea, and increase in bodyweight.Results There was no significant difference in the mean durationof the diarrhea in the synbiotic and probiotic groups, 3.92 days(SD 0.79) vs 3.80 days (SD 0.82) ,(Pô€€¸0.35), respectively. Nor didwe observe a significant difference in the mean increase in bodyweight in the synbiotic and probiotic groups, 150 g (SD 49.7) vs160 g (SD 48.9), (Pô€€¸ 0.67), respectively.Conclusion We observed no significant differences in efficacy ofsynbiotic and probiotic treatment for management of acute waterydiarrhea. [Paediatr Indones. 2012;52:209,12].